Total quality : management, organization, and strategy - Evans, James R. 1950- 4 0 (James Robert),16; 1956- Dean, James W.; 5 (Mason, OH : South-Western College Pub., 2000)
Total Quality: Management, Organization, and Strategy, 2e is organized according to traditional management topics, helping students to see the parallels between Quality Management and management theories in areas such as organizational design and leadership. Additional key features include: concise, direct, and current examples and cases are included in every chapter, providing the basis for productive classroom discussion. More than 25 new boxed examples demonstrate how real companies use total quality techniques discussed throughout the text.--BOOK JACKET
Pt. I. Introduction to Total Quality. 1. Introduction. 2. Approaches to Total Quality. 3. Total Quality Tools and Statistical Thinking -- Pt. II. Total Quality and Organization Theory. 4. Quality in Customer-Supplier Relationships. 5. Designing Organizations for Quality. 6. Total Quality and Organizational Change -- Pt. III. Total Quality and Organizational Behavior. 7. Quality Teamwork. 8. Empowerment and Motivation. 9. Quality Leadership -- Pt. IV. Total Quality and Strategic Management. 10. Total Quality and Competitive Advantage. 11. Strategic Planning and Total Quality Implementation
Dean's name appears first on the earlier edition
Includes bibliographical references and index
Keywords: 2 -- 0; 6; Total quality management. -- 20; 20; 2